QIRĀ’AH MU‘ĀṢIRAH MUḤAMMAD SYAḤRŪR ATAS AYAT-AYAT “MILK AL-YAMĪN” DAN “ZAWĀJ” - Fasjud Syukroni (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2019)
This article discusses Muḥammad Syaḥrūr's contemporary interpretation of verses of milk al-yamīn, which by classical interpretation means not far from the words al-raqīq, al-sarāri, al-īabīd, al-jawāri, and al-sabāyā. The interpretation is relative, non-standard and not final (read: only interpretation in the children of his time). This is understandable because the slavery system at that time still existed. For Syaḥrūr, the interpretation of